2016
DOI: 10.1002/2015jd024308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of post‐harvest crop residue fires on surface ozone mixing ratios in the N.W. IGP analyzed using 2 years of continuous in situ trace gas measurements

Abstract: O 3 , CO, and NO x affect air quality and tropospheric chemistry but factors that control them in the densely populated N.W. Indo-Gangetic Plain (IGP) are poorly understood. This work presents the first simultaneous 2 year long in situ data set acquired from August 2011 to September 2013 at a N.W. IGP site (30.667°N, 76.729°E; 310 m asl). We investigate the impact of emissions and meteorology on the diel and seasonal variability of O 3 , CO, and NO x . Regional post-harvest crop residue fires contribute majorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…A significant portion (16%) of the air mass, during pre-monsoon, originated from the IGP region. These air masses could carry the biomass burning emission from the IGP region at our site since agro residue burning is common during this season of the year over northwestern IGP region [46]. A recent study [18] has shown that the site over Himalayan foothills gets influenced by biomass burning on either side (east or west) of Indo-Gangetic Plain.…”
Section: Hysplit Back Trajectory Analysismentioning
confidence: 88%
“…A significant portion (16%) of the air mass, during pre-monsoon, originated from the IGP region. These air masses could carry the biomass burning emission from the IGP region at our site since agro residue burning is common during this season of the year over northwestern IGP region [46]. A recent study [18] has shown that the site over Himalayan foothills gets influenced by biomass burning on either side (east or west) of Indo-Gangetic Plain.…”
Section: Hysplit Back Trajectory Analysismentioning
confidence: 88%
“…Extensive agricultural burning in this area lasts for more than 3 weeks during every post-monsoon season, causing the smoke to spread widely like a blanket over nearly the whole IGP (Fig. 10), with very high O 3 and CO loadings (Kumar et al, 2016) and particulate matter concentrations (Rastogi et al, 2016). Concerning the situation in Lumbini, the flow of air mass is dominated by westerlies in post-monsoon season.…”
Section: Sources and Regional Transportmentioning
confidence: 99%
“…In the emission source region, diurnal variations of primary pollutants provide information about the time-dependent emission activities (Kumar et al, 2016b). Figure 5 shows the diurnal variation of hourly averaged concentrations of measured pollutants during the sampling period.…”
Section: Diurnal Variations Of Air Pollutants and Boundary Layer Heightmentioning
confidence: 99%
“…Morning and evening periods experienced the winds coming from the southeastern direction while the winds were predominantly from the southwestern direction during late afternoon. The increase in CO concentrations in the evening hours might be due to transport of CO from source regions upwind of Lumbini, which, along (Kumar et al, 2016b). The PBL height (in meters) was obtained from the WRF model as observations were not available.…”
Section: Diurnal Variations Of Air Pollutants and Boundary Layer Heightmentioning
confidence: 99%
See 1 more Smart Citation